Novel function of transcription factor Uga3 as an activator of branched-chain amino acid permease BAP2 gene expression - Muñoz, Sebastian Anibal (2019)
Transcription regulation of most genes in yeast occurs at the level of activation, i.e. the basal level of expression is very low and increased transcription requires gene-specific transcription factors allowing the recruitment of basal transcriptional machinery. Saccharomyces cerevisiae BAP2 gene encodes the permease responsible for the major part of leucine, valine and isoleucine uptake, amino acids that this yeast can use as nitrogen sources. Moreover, BAP2 expression is known to be induced by the presence of amino acids such as leucine. In this context, the current results show that BAP2 is an inducible gene in the presence of nitrogen-poor source proline but exhibits high constitutive non-inducible expression in nitrogen-rich source ammonium. BAP2 expression is regulated by the SPS sensor system and transcription factors Leu3, Gcn4 and Dal81 in both a direct and an indirect way depending on the quality of the nitrogen source. We further demonstrate here that a physical interaction occurs between Uga3 ‒the transcriptional activator responsible for γ-aminobutyric acid (GABA)-dependent induction of the GABA genes‒ and the regulatory region of the BAP2 gene, which leads to a strong positive regulation.